Issledovanie socetannogo vlijanija trenirovok myšc šei i elektrotrankvilizacii central'noj nervnoj sistemy na statokineticeskuju ustojcivost' operatorov skorostnych dinamiceskich ob"ektov - Lysenko, A. V.; Stepanova, T. A.; Buynov, L. G.; Sorokina, L. A. (Theory and Practice of Physical Culture, 2018)
The study analyzes benefits of the combined effects of the neck muscle trainings and central nervous system electric tranquillization (CNSET) tools on the equilibrium sense of the fast-moving system operators. The study was completed at an aviation school and timed to the scheduled medical examination of the entrants. Sampled for the study were the 17-18 year-old individuals, with the uninterrupted Coriolis effect accumulation tolerance test rates of less than 2min. The Experimental Group (EG) was subject to special neck training practices (NTP) and central nervous system electric tranquillization (CNSET) practices. The Reference Group was subject to placebo CNSET sessions only, without NTP. Both of the groups were tested straight after and 1, 2 and 3 months after the CNSET and NTP cycles.